Хлопушка с прицелом - Новицкий Евгений Игоревич (Детектив-Ностальгия, 2023)
Экземпляры: ЦБ (20230511) / Инвентарный номер: 58868 / Цена: 363.08 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Н 73 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44